Catenated (Bi)n (n=2, 3, 4) Complexes with Formally Monovalent Bismuth Centres. Issue 19 (19th September 2022) - Schwamm, Ryan J.; Kilpatrick, Alexander F. R.; Coles, Martyn P.
Abstract: The reduction of Bi(III) and Bi(II) compounds supported by the NON R ‐ligand (NON R =[O(SiMe2 NR)2 ] 2− ; R=Dipp=2, 6‐ i Pr2 C6 H3, t Bu) afforded species in which the metal was present in a range of formal oxidation‐states. Cyclic voltammetry performed on the Bi(II) radical [Bi(NON Dipp )]⋅ indicated that the Bi(I) oxidation state was accessible, although the lifetime of the resultant species was short. Preparative scale reactions of Bi(NON Dipp )Cl and excess LiBEt3 H afforded the tetrametallic cluster Bi4 (NON Dipp )2, in which the bismuth atoms form a [1, 2]‐edge missing tetrahedron. Reduction of the dibismuthane [Bi(NON t Bu )]2 with potassium in the presence of [2.2.2]‐cryptand generated a tribismuthinide salt containing the [Bi(NON t Bu )2 ( μ ‐Bi)] − anion and a non‐coordinating [K([2.2.2]‐crypt)] + cation. Reduction of isolated [Bi(NON Dipp )]⋅ with the Mg(I) reagent [Mg(BDI Dipp )]2 (BDI Dipp =[HCC(Me)NDipp2 ] − ) formed the dibismuthene [Bi( μ ‐NON Dipp )Mg(BDI Dipp )(THF)]2, with a crystallographically verified Bi=Bi multiple bond. Abstract :